Effects of microwave processing in comparison to sous vide cooking on meat quality, protein structural changes, and in vitro digestibility - Gawat M; Boland M; Chen J; Singh J; Kaur L (Elsevier Ltd, 2024)
This study investigated the effect of industrial microwave (MW) processing, and sous vide (SV) on goat and lamb biceps femoris, where samples were cooked to the same tenderness. The cooked meat quality and ultrastructure were analyzed along with determining the protein surface hydrophobicity, particle size distribution, secondary structure, and protein digestibility. MW-processing resulted in higher cooking loss and more ultrastructural damage than SV and also induced higher myofibrillar protein surface hydrophobicity. Both processes caused a significant increase (p < 0.05) in the β-sheet and an increase in the random coils with a reduction (p < 0.05) in α-helix and β-turns. Both processes led to different protein hydrolysis patterns (observed through SDS-PAGE), but overall free amino N release after digestion was not significantly different among them. The results suggest that MW and SV modify meat protein structure differently, but with the same meat tenderness level, these processes can lead to similar overall protein digestibility.
Keywords: FTIR spectroscopy; Meat digestion; Meat ultrastructure; Microwave processing; Protein aggregation; Protein surface hydrophobicity